2016 7th International Conference on Mechanical and Aerospace Engineering (ICMAE) 2016
DOI: 10.1109/icmae.2016.7549526
|View full text |Cite
|
Sign up to set email alerts
|

The influence of secondary flow structures in a turbocharger turbine housing in steady state and pulsating flow conditions

Abstract: Abstract-This paper presents a computational investigation into the effect of volute secondary flow structures on turbine inlet flow conditions. The steady state results show Dean type vortices exist early in the volute. As a result a substantial variation in absolute flow angle at the volute exit was observed. Pulsed flow simulations showed that the size and position of the secondary flow structures are time dependent. The resulting volute exit flow conditions were also found to be time dependent with the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…This behavior is the result of the development of flows within the volute and was discussed previously by Lee et al 9 Figure 24 shows contours of radial velocity and surface streamlines on six planes around the volute at 40 Hz pulse frequency at both the minimum and maximum incidence running points. The positions of the six planes are 54 , 72 , 90 , 126 , 198 and 270 .…”
Section: Operating Conditionssupporting
confidence: 64%
See 1 more Smart Citation
“…This behavior is the result of the development of flows within the volute and was discussed previously by Lee et al 9 Figure 24 shows contours of radial velocity and surface streamlines on six planes around the volute at 40 Hz pulse frequency at both the minimum and maximum incidence running points. The positions of the six planes are 54 , 72 , 90 , 126 , 198 and 270 .…”
Section: Operating Conditionssupporting
confidence: 64%
“…The development of volute secondary flows in a circular cross sectioned volute was investigated by Lee et al 9 under both steady state and pulsating flow conditions. The authors found Dean-like vortex development in the volute and a significant variation in volute outflow conditions as a result.…”
Section: Introductionmentioning
confidence: 99%
“…The development of volute secondary flows in a circular cross sectioned volute was investigated by Lee et al [13] under both steady state and pulsating flow conditions for a radial turbine. The authors found Dean-like vortex development in the volute and a significant variation in volute outflow conditions as a result.…”
Section: Introductionmentioning
confidence: 99%
“…They will entangle each other and a new swirling flow will emerge downstream of the junction. This new swirling flow plays a decisive role in the performance of LPT [13]. The swirling flow is deeply influenced by the bypass flow in such a case, thus the bypass flows with different injected locations are expected to diversely influence the turbine performance.…”
Section: Introductionmentioning
confidence: 99%